Pengembangan User Interface Dan User Experience Aplikasi BNI Mobile Banking Menggunakan Metode User Centered Design (Studi Kasus Aplikasi Bni Mobile Banking) - Hedi Yusuf (PT. INOVASI TEKNOLOGI KOMPUTER, 2023)
As one of the biggest banking companies in Indonesia, Bank Negara Indonesia (BNI) needs to innovate and face the new challenges of the digital era revolution. Mobile banking apps is a crucial component that is currently needed by and being used by most citizen in this era. To become a competitive banking app, many aspects need to be considered and continuously improved; one of them being the comfort and convenience of users in using the application through user interface and user experience (UI/UX) research and development. Unfortunately, users still experience issues and complaints while using this app that can be found in the Google Play Store and Apple App Store review columns. Data taken using the System Usability Scale (SUS) questionnaire in the current application condition also showed poor results. This research focuses on improving the usability of the application and answering user complaints through interface redesign on the features most used by users using the User Centered Design (UCD) approach. The redesigned results will then be tested using the usability testing method and successfully obtained a positive score of 94. The SUS score also significantly went up from 54 to 90.5. Therefore, this research can be concluded as successful with positive results and went according to plan